2022
DOI: 10.3390/ijms23158727
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-5 Receptor: Pharmacology and Its Regulation of Energy Metabolism

Abstract: As the most recent melanocortin receptor (MCR) identified, melanocortin-5 receptor (MC5R) has unique tissue expression patterns, pharmacological properties, and physiological functions. Different from the other four MCR subtypes, MC5R is widely distributed in both the central nervous system and peripheral tissues and is associated with multiple functions. MC5R in sebaceous and preputial glands regulates lipid production and sexual behavior, respectively. MC5R expressed in immune cells is involved in immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 170 publications
0
4
0
Order By: Relevance
“…Moreover, activated MC5R can stimulate lipid mobilization in adipocytes and glucose uptake in skeletal muscle [35]. It has been shown that the binding of α-MSH to MC5R activates the PKA and ERK1/2 (MAPK) signaling pathways, and the activation of MC5R in skeletal muscle regulates fatty acids oxidation in muscle cells through PKA and MAPK signaling pathways [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activated MC5R can stimulate lipid mobilization in adipocytes and glucose uptake in skeletal muscle [35]. It has been shown that the binding of α-MSH to MC5R activates the PKA and ERK1/2 (MAPK) signaling pathways, and the activation of MC5R in skeletal muscle regulates fatty acids oxidation in muscle cells through PKA and MAPK signaling pathways [36].…”
Section: Discussionmentioning
confidence: 99%
“…Melanocortins are derived from tissue-specific posttranslational processing of the common precursor—proopiomelanocortin (POMC) [ 2 ]. The melanocortins are involved in pleiotropic physiological functions, including pigmentation, adrenal steroidogenesis, appetite regulation and energy homeostasis, energy metabolism, cardiovascular function, exocrine secretion, inflammation, immunomodulation, neuromuscular regeneration, sexual function, and temperature control [ 3 , 4 , 5 , 6 , 7 , 8 ]. Recent FDA approval of melanocortin-based drugs is expected to further promote the investigation of the melanocortin system and lead to new pharmacotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…As a single transmembrane protein that forms a homodimer, MRAPs may interact with and regulate the trafficking and signaling of all MCRs ( Chan et al, 2009 ). In numerous vertebrates, MCRs interact with MRAPs and play a role in pigmentation, lipolysis, adrenal steroidogenesis, energy homeostasis, immunology, and cardiovascular function ( Cooray and Clark, 2011 ; Dores et al, 2016 ; Scanes and Pierzchala-Koziec, 2021 ; Ji et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%